WRITING: GLOBAL PROBLEM AND CONCERN - Tatyana D. Venediktova (Высшее образование в России)
Writing research as a new field of analytical work and writing as practical pedagogy addressing the needs of the broad spectrum of students are discussed, with particular attention to the results of the international congress “Writing research across borders” (Paris, February 18-22, 2014).